Epidemiology of poisonings, fractures and burns among 0–24 year olds in England using linked health and mortality data - Baker, Ruth; Orton, Elizabeth; Tata, Laila J.; Kendrick, Denise (Oxford University Press, 2016)
Background: Understanding patterns of injury in England is challenging due to a lack of national injury surveillance data. Through recent linkage of a large primary care research database to hospitalization and mortality data, we describe the epidemiology of poisonings, fractures and burns over a 14-year period.